ANALISIS FAKTOR-FAKTOR KESULITAN MEMBACA DAN BERHITUNG PERMULAAN SISWA DI SD NEGERI GEDONGKIWO - Rahmawati, Putri; kurniawati, Wahyu (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
The research was conducted with the aim of analyzing the factors of students' initial reading and numeracy difficulties at Gedongkiwo State Elementary School. Research subjects are determined by purposive sampling, namely by deliberately selecting subjects by researchers according to certain objectives and criteria. The subjects used in the research were teachers and class II students. Data collection in this research used descriptive qualitative research. The techniques and instruments used for data collection used interviews, observation and documentation. This journal tries to describe the analysis of the factors of students' initial reading and numeracy difficulties at Gedongkiwo State Elementary School. The results of this research showed that there were several elementary school students who could not read and count, some could read fluently, but there were still students who had to spell letters in syllables. Of the 37 students, there are 8 students who still experience difficulties in reading and arithmetic, because they still cannot remember letters and still need guidance from the teacher. The types of reading difficulties are, students do not know letters, students have difficulty spelling letters, syllables, have not memorized letters, cannot read syllables into words, and have difficulty distinguishing letters that have almost the same shape. Then the types of difficulties in counting are, difficulty saying numbers, difficulty calculating addition and subtraction, difficulty calculating with large numbers, and not understanding the meaning of counting.